Manipulation of light quality is an effective tool to regulate photosynthetic capacity and fruit antioxidant properties of Solanum lycopersicum L. cv. ‘Microtom’ in a controlled environment - Ermenegilda Vitale; Violeta Velikova; Tsonko Tsonev; Giulia Costanzo; Roberta Paradiso; Carmen Arena (PeerJ, 2022)
Light quality plays an essential role in setting plant structural and functional traits, including antioxidant compounds. This paper aimed to assess how manipulating the light spectrum during growth may regulate the photosynthetic activity and fruit bioactive compound synthesis in Solanum lycopersicum L. cv. ‘Microtom’ to improve plant physiological performance and fruit nutritional value. Plants were cultivated under three light quality regimes: red-green-blue LEDs (RGB), red-blue LEDs (RB) and white fluorescent lamps (FL), from sowing to fruit ripening. Leaf functional traits, photosynthetic efficiency, Rubisco and D1 protein expression, and antioxidant production in fruits were analyzed. Compared to FL, RGB and RB regimes reduced height and increased leaf number and specific leaf area, enhancing plant dwarf growth. The RGB regime improved photosynthesis and stomatal conductance despite lower biomass, favoring Rubisco synthesis and carboxylation rate than RB and FL regimes. The RB light produced plants with fewer flowers and fruits with a lower ascorbic acid amount but the highest polyphenol content, antioxidant capacity and SOD and CAT activities. Our data indicate that the high percentage of the green wavelength in the RGB regime promoted photosynthesis and reduced plant reproductive capacity compared to FL and RB. Conversely, the RB regime was the best in favoring the production of health-promoting compounds in tomato berries.